The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.4103/0301-4738.40362
|View full text |Cite
|
Sign up to set email alerts
|

Practical approach to medical management of glaucoma

Abstract: Primary open angle glaucoma (POAG) is usually a chronic, slowly progressive disease. At present, all resources are directed towards reduction of intraocular pressure (IOP), the only known causal and treatable risk factor for glaucoma, and medical management is frequently the first choice in most cases. With the introduction of innovative tools for early diagnosis and newer medications for treatment, decision-making in diagnosis and treatment of glaucoma has become more complex. The philosophy of glaucoma manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…A study that evaluated these QOL issues categorized patients mainly into two groups based on their main priorities as “reading and seeing detail” and “outdoor mobility”, the latter changing to the former with increasing visual field loss and an increased willingness to trade time off for therapy thus resulting in a situation of forced compliance (Aspinall et al 2008). Considering this, it is remarkable how, the entire viewpoint of treating glaucoma has gradually changed to preserving “visual function” while ensuring minimal effects on QOL in terms of cost, treatment regime, follow-up schedules as well as socio economic burden (Janz et al 2001; Parikh et al 2008). …”
Section: Treatment Decisions and Effects On Quality Of Lifementioning
confidence: 99%
“…A study that evaluated these QOL issues categorized patients mainly into two groups based on their main priorities as “reading and seeing detail” and “outdoor mobility”, the latter changing to the former with increasing visual field loss and an increased willingness to trade time off for therapy thus resulting in a situation of forced compliance (Aspinall et al 2008). Considering this, it is remarkable how, the entire viewpoint of treating glaucoma has gradually changed to preserving “visual function” while ensuring minimal effects on QOL in terms of cost, treatment regime, follow-up schedules as well as socio economic burden (Janz et al 2001; Parikh et al 2008). …”
Section: Treatment Decisions and Effects On Quality Of Lifementioning
confidence: 99%
“…[5] With the introduction of innovative tools for early diagnosis and newer medications for treatment, diagnosis and treatment of glaucoma has became more complex. [6] The newer glaucoma medications have advantages like increased efficacy, reduced dosing frequency, and improved side effect profile. Studies related to drug utilization in glaucoma reported from India are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In our own clinical routine: we use the "Overview" and glaucoma progression analysis (GPA) programs. 3 Eyeballing the overview we get a feel for whether field deterioration is due to generalized sinking of the hill of vision or whether it is due to glaucoma. GPA is based on the pattern deviation plot and is better option to diagnose progression.…”
Section: Progression On Visual Fieldsmentioning
confidence: 99%